Citizen-centric adoption model for smart government among United Arab Emirates public users - Alhosani, Fahad Ismail Ahmed Khalifa (2023)
Tremendous advancements in information and communication technology, coupled with the usability of smart mobile devices, have brought enormous growth in the appeal of highquality government services. This appeal has, in turn, encouraged governments to deploy services to citizens using a smart government channel. Worldwide, governments have recognized the need to deliver better-integrated services to the public to meet their expectations. Therefore, the transition from the conventional modes of delivering government services to a smart government format involves substantial considerations in the operational aspects of services delivery and drastic changes in existing core business systems across governmental public institutions. The concepts of smart government and smart services have emerged as new ways to deliver such services to meet citizens’ demands by developing tools and setting practical standards for services delivery. However, the smart government concept is still difficult to adopt in developing countries including United Arab Emirates (UAE) among public users. Although preparations for adopting the smart government concept in UAE have started running, the implementation of this concept is still not optimal.This means that most smart government studies are still focusing on problems in the early stages of the adoption phase. Thus, this study proposes a Citizen-Centric Adoption Model for Smart Governments among UAE Public Users. There are three objectives of this study. The first objective is to determine the attributes of a citizen-centric design model in smart government. Second, to build a new citizen-centric design model for adoption in the UAE smart government among public users. Third, to validate the proposed model in a smart government among public users. The study opted for an exploratory study using a systematic literature study to identify the significant attributes of the proposed model. The research study was conducted in UAE with an estimated sample size of 323 respondents. To develop a citizen-centric model towards public users when using the online information of a smart government, the data were analyzed based on the regression model to test six hypotheses. The results derived show significant values on openness, transparency, responsiveness, usability, and trust, which recorded p-values of 0.010, 0.000, 0.006, 0.005 and 0.000, respectively that implies a significant relationship with influence on enhancing the citizencentric model is accepted, while the hypothesis related to security factor is rejected. Based on the hypothesis testing and analysis, there is a strong relationship between the significant attributes of the proposed model with the significant R-value. Overall, the adoption of a citizen-centric model in enhancing the public user experience when using online information of a smart government can be used by government agencies as helpful resources while adopting a smart government.